Health Risk Linked to the Consumption of Fish from Lake Tshangalele in the Sout-East of the Democratic Republic of Congo (London Journal of Research In Science: Natural and Formal, 2025)
Lake Tshangalele is a reservoir formed in 1930 from the Lufira River in the south-east of the Democratic Republic of the Congo for the construction of the Mwadingusha Dam. This lake is very rich in fish. Unfortunately, for several decades, it received mining waste from the metallurgical plants in the cities of Likasi and Kambove.To assess the health risk associated with the consumption of Lake Thangalele, fish samples were taken from the lake at the site of the locality of Kapolowe-Mission (n=21). And samples of reference fish were taken in a upstream of any mining activity of the Panda and Kasungwe rivers as well as of the Congo River at the level of the sections located near their sources (n=11). Then, after the sampling, a survey was carried out among 148 permanent inhabitants of Kapolowe-Mission which made it possible to understand the average quantity of fish that each of these 148 interviuwed people consumed per day in their family. Then, of these 32 samples, 11 TMEs, namely Al, As, Cd, Co, Cu, Mn, Ni, Pb, Se, U and Zn, were assayed by Inductively Couple Plasma Mass Spectrometry (ICP-MS) at the Catholic University of Leuven in Belgium and by Inductively Couple Plasma Optical Emission Spectroscopy (ICP-OES) at the laboratory of the Congolese Control Office (OCC) in Lubumbashi in Democratic Republic of Congo. And finally, for 5 trace metal elements, namely Cd, Cu, Ni, Pb, Zn, the health risk was evaluated, which is expressed by the DQ hazard quote. This is calculated for the oral route on the basis of the formula DQ=FxQx0.208xC/ADI x P. If DQ is greater than 1, it means that there is a good chance that it has been harmful to the health of the consumer. On the other hand, if the DQ value is less than 1, it means that there is no potential health risk associated with the consumption oh fish.This study showed us that the fish from Lake Tshangalele is not suitable for human consumption since by consuming this fish 81,7% of adults and 1OO% of children have a high risk of suffering the potental of harmful effects of only 5 trace metal elements studied, which are Cu, Ni, Pb, Zn and Cd, without taking into account the other possible pollutants non measured. It showed also that when humans consume fish from an aquatic ecosystem polluted by mining waste, they are likely to suffer the potential harmful effects of all possible pollutants carried by the mining waste and having contaminated the fish, given that their potental harmful effects tend to add up.
Keywords: Mangifera indica; HPTLC; quality control; polyphenols; Mangiferin; mass spectrometry; flavonoids; phytochemical standardization.; website visibility; agricultural research institutes; webometrics; digital presence; Casimir; Coulomb; Vacuum Quantum Energy Extraction; Piezoelectric; MEMS; Desarrollo; Regi????maz????a; Pobreza rural.